Grain-size mineral analysis of verdete rock coarse and fine aggregates and adjustment to two granulometric distribution models - Madeira, Aline Amaral (Eclética Química, 2020)
The supremacy of the mineral industry added to the necessity to supply the world market demand justifies the continuous research efforts for optimizing of the activities of mineral resource utilization. In an approach of mineral characterization, a grain-size analysis study of coarse and fine aggregates of verdete rock was presented in this work. The particle size distribution (PSD) of two samples of aggregates with granulometry < 2.36 mm was experimentally obtained using sieving techniques and adjustment to Rosin-Rammler-Bennet (RRB) and Gates-Gaudin-Schuhmann (GGS) granulometric distribution models. Both RRB and GGS models regressed well to the experimental data, presenting correlation coefficient values were extremely close between them approximately 0.99. The PSD’s results indicated that 65.97% dry aggregates and 67.68% wet aggregates had a particle size with mean diameter > 0.0050 mm; a similar behavior of the grain-size distributions presented by dry and wet aggregates; and a tiny presence of fine particles natural in the analyzed ore sample. The results suggested the suitability of the methodology to predict the grain-size performance the verdete ore beyond to show itself as a contribution to the enriching of the mineral characterization of the studied rock, as a potassium potential source for the mineral processing Brazilian industry.